Amino Acid and Peptide‐Based Antiviral Agents. (3rd August 2021) - Skwarecki, Andrzej S.; Nowak, Michał G.; Milewska, Maria J.
Abstract: A significant number of antiviral agents used in clinical practice are amino acids, short peptides, or peptidomimetics. Among them, several HIV protease inhibitors (e. g. lopinavir, atazanavir), HCV protease inhibitors (e. g. grazoprevir, glecaprevir), and HCV NS5A protein inhibitors have contributed to a significant decrease in mortality from AIDS and hepatitis. However, there is an ongoing need for the discovery of new antiviral agents and the development of existing drugs; amino acids, both proteinogenic and non‐proteinogenic in nature, serve as convenient building blocks for this purpose. The synthesis of non‐proteinogenic amino acid components of antiviral agents could be challenging due to the need for enantiomerically or diastereomerically pure products. Herein, we present a concise review of antiviral agents whose structures are based on amino acids of both natural and unnatural origin. Special attention is paid to the synthetic aspects of non‐proteinogenic amino acid components of those agents. Abstract : The antiviral fundamentals : Amino acid‐based building blocks are widely used in modern medicinal chemistry. Many antiviral agents incorporating amino acid residues of both natural and unnatural origin have been reported and approved by FDA as drugs. In this review, we summarize the synthetic aspects of amino acid‐based building blocks that could be found in popular antiviral drugs as well as drug candidates and other antiviral potent inhibitors.